A collaborative higher education initiative for leadership development: Lessons for knowledge sharing - Albertyn, R.; Frick, L. (South African Journal of Higher Education, 2016)
The higher education sector needs to prepare youth for the fast changing innovative focused economy. Visionary leadership is needed to facilitate this knowledge transfer for novelty creation. A collaborative initiative could facilitate leadership development and foster knowledge sharing in this context. The initiative with three stakeholder groups started with an Interactive Qualitative Analysis exercise to identify needs and formulate a collaboration charter to ensure reciprocal benefits. A programme evaluation research design was applied three years after implementation using a logic-model framework. Process evaluation entailed collecting data from 103 questionnaires and 11 semi-structured interviews. Based on interpretation of data according to an integrated framework for managing knowledge across boundaries, we identified three areas for further development: contextual knowledge, collaborative partnerships and common vision. Working collaboratively across institutional and knowledge boundaries towards a common vision could enhance leadership development and contribute to longer-term transformation and sustainable change in complex environments.